Control and Resolution Mechanisms of the Inflammatory Response 2016 - Baizabal Aguirre, Víctor M. (2016)
In the last 20 years the field of the innate immunity has advanced notably since the pioneering work on the discovery of Toll-like receptors. A considerable number of studies on the molecular mechanisms triggering the inflammatory response have been described. A search in PubMed with the words ?inflammatory response? for the current year gives 11,000 articles, which means an approximate 917 articles per month and 30 per day. This amount of information reflects the interest of the scientific community not only to understand the essential mechanisms involved in the inflammatory response but also to translate this knowledge for the treatment of chronic and degenerative human diseases. Now that the main participating molecules and signaling transduction mechanisms activated during the inflammatory response have been established, researchers have begun to elucidate how a tissue is able to control/resolve inflammation and regain homeostasis. This is because a failure of the mechanisms that self-regulate and resolve the inflammatory process may lead to chronic inflammation, and this in turn may cause degenerative diseases such as cancer, diabetes, and autoimmune and cardiovascular diseases. Although many investigations have described synthetic or natural molecules that inhibit inflammation, no clear picture on the control and resolution mechanisms have emerged. This special issue is an attempt to contribute to our knowledge of the molecular programs used by the cell to control and resolve inflammation. We hope this issue may be a good reference to all interested in the complex process of the inflammation control and resolution.